ANALISIS PENGARUH FLEKSIBILITAS JAM KERJA, UPAH, USIA, JENIS KELAMIN, DAN PENDIDIKAN MENJADI PENGEMUDI OJEK DARING DI KOTA MALANG - Fikri Aziz, Zulfikar; Athoillah, Moh. (Journal of Development Economic and Social Studies, 2023)
Ojek Online is an alternative job that can reduce unemployment. This study aims to analyze the effect of flexibility in working hours, wages, age, gender, and education to become online motorcycle taxi drivers in Malang City. Online motorcycle taxi partner survey data were analyzed using Iogit binary regression. The results showed that flexibility of working hours and education had an effect on online motorcycle taxi workers, while wages, age and gender had no effect on online motorcycle taxi workers. This research has implications that online motorcycle taxi jobs can provide many benefits so that online motorcycle taxi partners are interested in working.